Entrepreneurial ecosystem affects organisational learning, creativity and success - Khuong Ngoc Mai; Van Thanh Nguyen (Cogent Business & Management, 2023)
Entrepreneurship, a catalyst for advanced economies, yields widespread societal advantages through successful ventures. Amidst this, scholars and practitioners ardently contribute to a burgeoning knowledge repository, aiming to augment the triumph rate of startups. This study focalises on learning and creativity, pivotal facets for entrepreneurial accomplishment, and advances a theoretical framework elucidating the startup ecosystem's role in organisational learning and creativity. The World Economic Forum's (2013) model, encompassing six factors-Accessible Market, Workforce, Support System, Regulatory Framework, Education and Training, Cultural Support-comprises the entrepreneurial ecosystem examined. Our dataset, culled from surveys of 200 SME and startup founders or CEOs in Tay Ninh City, Vietnam, with at least five years of operational history, informs our study. Employing SmartPLS 3.0 and PLS-SEM methodology, empirical analysis unveils significant impacts: two ecosystem factors and organisational learning and creativity influence entrepreneurial success. Organisational learning engenders notable effects from the accessible market and workforce, while creativity draws impetus from accessible market, education and training, and support systems. Notably, organisational learning bolsters creativity within startups. These insights carry implications for catalysing regional entrepreneurship.
Keywords: 650; entrepreneurial ecosystem; entrepreneurial success; entrepreneurship; organisational creativity; organisational learning